Properties and sintering behaviour of fine spherical iron powders produced by new hydrogen reduction process. (July 2014) - Walther, G.; Büttner, T.; Kieback, B.; Weißgärber, T.; Hoffmann, M.; Bachmann, G.
<x content-type="archive" xml:space="preserve">Abstract</x> The most important use of fine spherical iron powders is for metal injection moulding (MIM). For many applications, the high costs of powder based on the carbonyl or atomising production route are a limiting factors. An alternative two-step hydrogen reduction process using a granulated hematite powder, which is a recycling product from steelmaking, has been developed to produce <25 µm spherical powder. The morphology and properties of the powder have been found to depend strongly on the second temperature step of the reduction process. A further important step is enclosed powder processing by milling and sieving to remove agglomerates. The powder properties and sintering behaviour as a function of heat treatment and processing parameters are reported and discussed.